Martensitic Phase Transformation and Deformation Behavior of Fe–Mn–C–Al Twinning‐Induced Plasticity Steel during High‐Pressure Torsion1. Issue 7 (5th February 2014) - Yan, Kun; Bhattacharyya, Dhriti; Lian, Qi; Kabra, Saurabh; Kawasaki, Megumi; Carr, David G.; Callaghan, Mark D.; Avdeev, Maxim; Li, Huijun; Wang, Yanbo; Liao, Xiaozhou; Langdon, Terence G.; et al.
<x xml:space="preserve">Abstract</x> The transformation between the face centered cubic austenitic and hexagonal close‐packed martensitic phases during high‐pressure torsion processing was observed in a Fe–Mn–C–Al twinning‐induced plasticity steel. This phase transformation was not found in the same material processed by unidirectional compressive and tensile deformation. Initiated by the high‐pressure loading, the martensite phase initially increased with torsional strain but diminished subsequently. Texture evolution of the austenitic phase was compared with the ideal texture distribution of face‐centered cubic materials after shear deformation.